Pengaruh Penyerapan Tenaga Kerja Terhadap Tingkat Kemiskinan di Kabupaten Purwakarta Periode 2011 – 2020 - Erika Yustitia; Arief Mulyawan Thoriq; Hamdan Ardiansyah (Masoem University, 2022)
Labor absorption in Purwakarta Regency is still fluctuating, though it is increasing. This has the potential to affect the level of poverty in Purwakarta Regency. The poverty rate in Purwakarta Regency varies, but it tends to decrease year after year. As a result, the purpose of this study is to determine the correlational relationship between labor absorption variables and poverty variables over a period of ten years. The Zamrowi theory was used for the employment variable, while the Central Statistics Agency theory was used for the poverty variable. This study employs a quantitative approach with secondary data from 2011 to 2020. The information used was obtained from BPS, Bappelitbangda, and the Manpower and Transmigration Office. Statistical analysis is the data analysis technique used in this study. A simple linear regression test was performed. Data testing is done with the help of SPSS software when processing data. According to the test results, employment has a significant impact on the level of poverty in Purwakarta Regency. This demonstrates that labor absorption can help to alleviate poverty. The poverty rate will fall as employment rises. Thus, one method of alleviating poverty is to increase labor absorption by expanding employment opportunities.